How Children’s Sports Participation Influences School Engagement Levels - Yang Jiang; Bo Feng (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This longitudinal investigation delves into the influence of sports involvement on the scholastic engagement of both left-behind and migrant children within China. The findings elucidate a notable discrepancy in scholastic engagement levels, with left-behind children (M=4.34) and migrant children (M=5.65) exhibiting markedly lower levels compared to their urban counterparts (M=6.02). Furthermore, the results underscore a significant positive correlation between participation in sports activities and scholastic engagement among these demographic groups. The analysis further reveals that interpersonal competencies serve as a partially mediating factor in this relationship. Additionally, the study identifies various individual and familial factors that exert significant influence on scholastic engagement levels. This research underscores the constructive impact of sports involvement on scholastic engagement and accentuates the importance of interpersonal skills. At a societal level, educational institutions, communities, and administrative bodies should endeavour to enhance the accessibility and inclusivity of diverse sporting opportunities, while integrating public sports resources more comprehensively into the social fabric. On a national policy level, the establishment of a sports participation network that fosters collaboration among homes, schools, and communities emerges as a promising avenue for furthering these objectives.